A mesomechanical model for predicting the degradation in stiffness of FRP composites subjected to combined thermal and mechanical loading. (5th January 2016) - Shi, Shengbo; Gu, Liangxian; Liang, Jun; Fang, Guodong; Gong, Chunlin; Dai, Cunxi
Abstract: The mechanical properties of Fiber Reinforced Polymer (FRP) composites decrease with increasing thermal exposure temperature and time. A mesomechanical model was presented to predict the degraded behavior of FRP composites supporting a static compressive loading under high temperatures. The thermal softening, thermal decomposition of the matrix material and phase transition of the reinforced fibers were considered in the developed model, which adversely affect the stiffness properties of the composite material. Also, in order to evaluate the effect of high internal pressure on stiffness property, the bulk modulus was applied in the formulation of the mathematical model. High temperature compression experiments were conducted to measure the temperature-dependent elastic modulus. The accuracy of the model was further assessed by comparing simulated and experimental modulus. The reduction in stiffness properties of FRP composites at high temperatures can be roughly divided into three stages by analyzing the predicted temperature-modulus curve. Graphical Abstract: Highlights: Thermal softening, thermal decomposition and phase transition adversely affect the stiffness of polymer composites. Bulk modulus was applied to evaluate the effect of high internal pressure on stiffness properties. High-temperature stiffness of silica/phenolic composites degrades roughly in three stages. Failure modes of the composite specimens are similar at different temperature environments.